The chrysanthemum and the eagle : the future of U.S.-Japan relations - Satō, Ryūzō, 1931- (New York University Press, 1994)
Whether in the form of the ongoing automotive wars, books and films such as Michael Crichton's Rising Sun, or George Bush's ill-fated trip to Japan in 1991, frictions between the United States and Japan have been steadily on the rise. Americans are bombarded with images of Japan's fundamental "difference." At the same time, voices in Japan call for a "Japan That Can Say No" to American pressures. If the guiding principle of the Clinton administration is indeed "new values for a new generation," how will this be reflected in U.S.-Japanese relations? Convinced that no true solution to U.S.-Japanese frictions can be achieved without tracing these frictions back to their origin, Ryuzo Sato here draws on a binational experience that spans three decades in both the Japanese and American business and academic communities to do just that. An incisive personal look at one of the most important political and economic global relationships, written by a major player in the world of international business and finance, The Chrysanthemum and the Eagle provides a readable and engaging tour of U.S.-Japan relations, past and present